MORPHOLOGICAL AND FUNCTIONAL CHARACTERISTICS OF THE MAIN ARTERIES AND PULSE WAVE VELOCITY IN OLDER AGE INDIVIDUALS WITH ARTERIAL HYPERTENSION - G. G. Efremushkin; T. V. Filippova; N. A. Lomakina (Российский кардиологический журнал, 2014)
Aim. To study morpho-functional state and pulse wave velocity (PWV) in the main arteries (MA) in older patients with arterial hypertension (AH) and chronic heart failure (CHF).Material and methods. Totally 122 patients studied (30 female) with AH+CHF at the age of 60-90 y.o., mean age 76,8±1,3. All patients had AH of the 3rd stage, 32 had isolated systolic hypertension (ISAH). AH of the 1st grade had 32, 2nd grade — 12, 3rd grade — 28 pts. CHF was at 1-2 stage with mean functional class 1,85±0,06. Control consisted of 48 healthy individuals at the age 19-25 (20,6±1,5). All participants underwent EchoCG and Dopplerography of common carotid arteries (CCA), brachial (BA) and femoral (FA) arteries with measurement of the diameter (D), intima-media thickness (CIM), velocity and volume values. Results. In patients with AH minute volume was 40% higher than in healthy individuals: by 24,4% due to inotropic and by 15,6% — chronotropic reserves. Values of CIM and D in patients and in controls did not change with posture and were higher in patients. Velocity and share kinetic energy were lower in patients than in controls. PVW in MA in patients with AH was 54-60% faster than in controls. The relation of PWV CCA: BA — 1:4,4; CCA: FA — 1:6,4-6,9; BA: FA — 1:1,5, was the same in patients and controls. There was no correlation between PWV and CIM, D and BP in young patients. Also the positive correlation is found for the time of pulse wave and heart rate.Conclusion. PWV does not directly relate to MA rigidity. Probably it is more depended on the conditions of the regulatory mechanisms of cardiovascular system and their reaction on everchanging states of central and peripheral hemodynamics, as with degeneration processes of aging, and can be named as one of the parts in adaptive correction of hemodynamics in MA. The increase of PWV and its kinetic energy compensates the loss of of blood flow velocity and maintains its volume by the unit of time during rapid phase of circulation.